Handbook for working with children and youth : pathways to resilience across cultures and contexts - Ungar, Michael, 1963- (Counseling and psychotherapy transcripts, client narratives, and reference works., 2005)
"The Handbook for Working With Children and Youth: Pathways to Resilience Across Cultures and Contexts examines lives lived well despite adversity. Calling upon some of the most progressive thinkers in the field, it presents a collection of original writing on the theories, methods of study, and interventions that promote resilience. Unlike other works that have left largely unquestioned their own culture-bound interpretations of the ways children and youth survive and thrive, this volume explores the multiple paths children follow to health and well-being in diverse national and international settings. It demonstrates the connection between social and political health resources and addresses the more immediate concerns of how those who care for children create the physical, emotional, and spiritual environments in which resilience is nurtured." "Academics, graduate students, and professionals studying or working in human service fields such as human development and family studies, education, social work, child and youth care work, developmental psychology/applied developmental science, child psychiatry, nursing, and family therapy will benefit from this Handbook. In essence, anyone who works with youth or is interested in the developmental issues related to children and youth in clinical, residential, or community settings will find Ungar's Handbook to be of great value."--Jacket